2015
DOI: 10.1186/s13104-015-1390-7
|View full text |Cite
|
Sign up to set email alerts
|

Trigger factors in primary headaches subtypes: a cross-sectional study from a tertiary centre in Greece

Abstract: BackgroundPrevious studies have shown that common headache triggers contribute to the onset of headache attacks on predisposed individuals and are considered important in the prevention of headache. The aim of this study was to compare the different characteristics of triggers among the most common primary headache subtypes (migraine without aura, migraine with aura and tension type headache).MethodsA total of 116 headache patients of the neurology outpatient department of a tertiary hospital in Athens were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 53 publications
0
30
0
1
Order By: Relevance
“…Headache disorders, mainly the primary including migraine, tension type and cluster, are considered as major global health problems due to their high prevalence, chronicness and their substantial disability burden upon the sufferers [ 1 , 2 ]. The socioeconomic impact of headache is worsened by sufferers’ low tendency of seeking medical care for their headache despite the high prevalence [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Headache disorders, mainly the primary including migraine, tension type and cluster, are considered as major global health problems due to their high prevalence, chronicness and their substantial disability burden upon the sufferers [ 1 , 2 ]. The socioeconomic impact of headache is worsened by sufferers’ low tendency of seeking medical care for their headache despite the high prevalence [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent headache is a risk factor for future chronic headache and other pain syndromes [ 17 ]. The risk of developing headache is greater in individuals with a family history, smoking, high body mass index, sleeping problems, substance abuse, oversleeping, premenstrual period, stressful life events, hot/cold weather, menstruation, hanger and others [ 1 , 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although not all studies could find a link between weather factors and migraine [8,9], some studies have reported a significant correlation [5,10,11]. In a study conducted in Greece [3], the literature review highlighted the following most frequently mentioned trigger factors: stress, skipping meals, sleep deprivation and weather changes [12][13][14]. Examples of weather trigger factors were temperature changes, high humidity, high winds, sun glare and bright light, barometric pressure changes, stormy weather and extremely dry conditions [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Migraine was ranked as the third most prevalent disorder and seventh-highest specific cause of disability worldwide in the Global Burden of Disease Survey 2010 [2]. The term "headache (or migraine) trigger" is used to describe a stimulus that alone or in combination, contributes to the onset of a headache (or migraine) attack on predisposed individuals [3]. Knowledge about migraine trigger factors is important in the management of migraine because the avoidance of these factors may result in better control of the disorder [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation